Bond strength evaluation methods of RC members strengthened with FRP composites. (15th December 2021) - Slaitas, Justas; Valivonis, Juozas
Highlights: The universal fully analytical load-carrying capacity solution of RC members strengthened with EBR and NSM FRP reinforcements is proposed. The proposed method is based on the principles of the built-up bars theory and consists of analytical intermediate crack induced debonding solution, taking into account the concrete cracking nature. An extensive database of strengthened beam tests was used for experimental validation. An extended review of existing bond strength evaluation methods is performed. Abstract: This article examines the bond behaviour of reinforced concrete members and fibre-reinforced polymer reinforcements in the failure stage. Sudden and brittle debonding like failure modes are the most common for such elements. Therefore, a comprehensive review of the existing FRP and concrete bond strength models is provided. In view of the existing methods and the theoretical and experimental research carried out by the authors in recent years, a general analytical solution is proposed for the calculation of the load carrying capacity of FRP strengthened RC members in bending. The proposed method is based on the principles of the built-up bars theory and consists of analytical intermediate crack induced debonding solution, taking into account the concrete cracking nature. The main idea is to evaluate the reduction of overall member stiffness due to the slip between concrete and FRP by reducing the FRP stress with an analytically derived factor. Such a reduction allows to predict the load carrying capacity of strengthened members sufficiently precisely. The numerical results are compared with the experimental ones of beams in bending. The experimental database consists of a great variety of RC beams strengthened with externally bonded and near surface mounted CFRP, GFRP sheets, laminates, strips, and rods. Experimental results were collected from various scientific publications.